Getting What You Need: How Reputation and Status Affect Team Performance, Hiring, and Salaries in the NBA - Ertug, Gokhan; Castellucci, Fabrizio (Academy of Management Journal, 2013)
We study how the reputation and status of resource providers affect the two organizational outcomes of product quality and revenues, hiring decisions, and prices paid to resource providers. We argue that reputation and status have different effects on outcomes: reputation has a stronger effect on product quality, and status has a stronger effect on revenues. Building on this, we argue that actual quality mediates the effect of reputation on revenues more than the effect of status on revenues. Moreover, reputation and status have different effects on how organizations acquire resources: when their product quality is low relative to their aspiration level, organizations will display a preference for recruiting high-reputation resource providers over high-status ones. Conversely, organizations will display a preference for recruiting high-status resource providers over high-reputation ones when their revenue is low relative to their aspiration level. Finally, although both reputation and status have positive effects on the price paid for a resource, we argue that the relationship between reputation and pay is weaker for high-status resource providers. We find support for our hypotheses in a sample of NBA players and teams.